Electrochemical determination of iron in coastal waters based on ionic liquid-reduced graphene oxide supported gold nanodendrites. (10th September 2015) - Li, Fei; Pan, Dawei; Lin, Mingyue; Han, Haitao; Hu, Xueping; Kang, Qi
Highlights: IL-rGO is used as a support for electrochemical deposition of AuNDs. AuNDs shows superior electrochemical activity properties for iron. Sandwich structured IL-rGO/AuNDs/Nafion modified electrode has been obtained successfully. IL-rGO/AuNDs/Nafion modified electrode can be applied for iron determination in coastal waters. Abstract: An effective and sensitive method for electrochemical determination of iron was reported, based on the ionic liquid-reduced graphene oxide (IL-rGO) supported gold nanodendrites (AuNDs). IL-rGO as a soft support could provide large specific surface area for AuNDs and make them smaller sizes and unique forms, which would benefit to the electrochemical reduction of iron. Nafion is employed as a cation exchange polymer in which IL-rGO and AuNDs can be tightly attached to the electrode surface. The proposed sandwich structured IL-rGO/AuNDs/Nafion modified electrode shows excellent electrochemical properties. The IL-rGO/AuNDs/Nafion modified electrode combined individual advantages as a whole and showed good responses for iron ions. Under the optimized conditions, the reduction peak currents of iron have a good linear relation with its concentrations ranging from 0.30 to 100 μmol L −1 with the detection limit of 35 nmol L −1 . More importantly, this sandwich structured modified electrode had a good anti-interference ability and successfully applied in the determination of the total dissolved iron in coastal waters.